From Incoherence to Sustainability: Performance, Activism, and Social Media in the Most Recent Russian Poetry - Kirill Korchagin (Internationale Zeitschrift für Kulturkomparatistik)
This article considers the evolution of poetic performance on the basis of several Russian poets of the 2010s. The type of performance in question, which originally implied active absorption in the poetic text, occupied an important place in Russian art of the twentieth century – from the first experiments of the historical avant-garde to Moscow Conceptualism (above all, in the their “Collective Actions”). As such, it has always maintained a closeness to the poetic work and was most often practiced by poets who sought to extend their texts beyond the space of the page and into the “external” world. In the 2010s, however, with the development of social media, the opposite trend is noticeable – poets, while declaring their connection to the performative traditions of Moscow Conceptualism, transfer their performative activity into a textual space organized by social media platforms. The central hypothesis of this article is that all of these poets react differently to the methods of discursive organization provided (and enforced) by social networks and strive in different ways to liberate themselves from the censorship of the algorithm: some emphasize the discursive incoherence of the platform, while others, on the contrary, seek to develop a sustainable manner of uniting private discourses into a new totality.